A Comprehensive Depiction of the Furan‐Maleimide Coupling via Kinetic and Thermodynamic Investigations of the Diels‐Alder Reaction of Poly(styrene–co‐2‐vinylfuran) with Maleimides. Issue 4 (8th February 2017) - Buonerba, Antonio; Lapenta, Rosita; Ortega Sánchez, Sheila; Capacchione, Carmine; Milione, Stefano; Grassi, Alfonso
Abstract: Copolymers of styrene with 2‐vinylfuran (S‐ co ‐2VF) were reacted with maleimides to yield functionalized copolymers via Diels‐Alder (DA) reaction. The polymer compositions and the chemical structure of the DA cycloadducts were fully characterized by means of NMR spectroscopy. The kinetic and thermodynamic parameters were thus assessed for the DA and backward reaction (r‐DA) to gain information on this click reaction using a set of equations properly designed. The VT NMR monitoring of the reactions allowed to calculate the apparent rate constants for the formation and decoupling of the DA cycloadducts with both the endo and exo configurations in the range of temperature 70–120 °C. The activation energy barriers of 47.8 ± 5.6 kJ mol −1 and 174 ± 17 kJ mol −1 were calculated from the Arrhenius plots for the DA and r‐DA reactions, respectively. The Eyring‐Polanyi equation permitted also to assess the enthalpic and entropic contributions of 171 ± 17 kJ mol −1 and 0.09 ± 0.15 kJ K −1 mol −1 for the r‐DA reaction. The thermodynamic equilibrium constants yielded the enthalpy (‐157 ± 14 kJ mol −1 ) and entropy (‐370 ± 40 J K −1 mol −1 ) of formation of the DA cycloadducts. Abstract : Copolymers of styrene with 2‐vinylfuran were reacted with maleimides to yield functionalized copolymers via Diels‐Alder (DA) reaction. The polymer compositions and the chemical structure of the DA cycloadducts were fully characterized by means of NMR spectroscopy. The kinetic and thermodynamic parameters were thus assessed for the DA and backward reaction (r‐DA) to gain information on this click reaction using a set of equations properly designed.